Relation between severity of liver disease and renal oxygen consumption in patients with cirrhosis. Issue 1 (1st July 1999) - Gadano, A; Moreau, R; Heller, J; Chagneau, C; Vachiéry, F; Trombino, C; Elman, A; Denié, C; Valla, D; Lebrec, D
Abstract : BACKGROUND: Worsening cirrhosis may lead to increased renal O2 metabolism caused by activation of neurohumoral antinatriuretic substances. AIMS: To evaluate the relation between the severity of liver disease, sodium excretion, and neurohumoral antinatriuretic substances on the one hand and renal O2 metabolism on the other in patients with cirrhosis. METHODS: Renal O2 consumption and haemodynamics as well as plasma concentrations of noradrenaline, renin, and aldosterone were measured. Investigations were performed in 14 patients with Pugh's grade A, 43 with grade B, and 29 with grade C liver disease. RESULTS: Renal O2 consumption significantly increased with the severity of cirrhosis (grade A, 8.9 (1.6); grade B, 15.5 (1.3); grade C, 18.0 (1.5) ml/min/m 2 ). Plasma concentrations of noradrenaline, renin, and aldosterone significantly increased while mean arterial presssure and systemic vascular resistance significantly decreased with the severity of the disease. A significant inverse correlation was found between renal O2 consumption and sodium excretion. A significant direct correlation was found between plasma levels of noradrenaline and aldosterone on the one hand and renal O2 consumption on the other. Renal blood flow and the glomerular filtration rate did not differ significantly between patients with grade C and grade A or B disease. CONCLUSIONS: This study shows for the first time that, in patients with cirrhosis, worsening of the disease is associated with an increase in renal O2 consumption. The results suggest that increased renal O2 consumption is due to renal tubular sodium retention caused by increased levels of neurohumoral antinatriuretic substances. This neurohumoral activation is related to cirrhosis induced vasodilation.